ANALISIS NILAI TAMBAH (VALUE ADDED) PETERNAK DAN PEJAGAL ATAS BIAYA YANG DICIPTAKAN PADA PEMASARAN SAPI POTONG DI KECAMATAN LOLONG GUBA, KABUPATEN BURU, PROVINSI MALUKU - Adolf Heatubun; Marcus Veerman; Michel J. Matatula (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2020)
The concept of added value in agriculture has an important role in development, both production, consumption and trade. Producers, consumers, and market players take advantage of this concept to create productivity in their respective environments. This study aims to analyze the added value of the products created by beef cattle breeders and cattle slaughterers in Lolong Guba District, Buru Regency. The study used a survey method, the sample was selected by purposive sampling for the districts, breeders and slaughterers. The study was conducted from April to May 2020. The analysis used identification, measurement and ratio techniques. The results showed that value-added activities of breeders included herding and fattening cattles. For the slaughterers includes buying and slaughtering cattles and selling meat. The cost of the breeders includes providing forage, caring for and grazing the livestock. The cost of slaughtering includes the purchase, transportation, retribution and slaughter of cattles at arbatoir. The added value at cattle breeders is higher in comparison to slaughterers. Productivity creates added value at cattle breeders higher than slaughterers. Breeders are superior in raising livestock, while slaughterers are superior in frequency of slaughtering time.